Galectin functions in cancer-associated inflammation and thrombosis - Kruk, Linus; Braun, Attila; Cosset, Erika; Gudermann, Thomas; Mammadova-Bach, Elmina (Frontiers in Cardiovascular Medicine, 2023)
Galectins are carbohydrate-binding proteins that regulate many cellular functions including proliferation, adhesion, migration, and phagocytosis. Increasing experimental and clinical evidence indicates that galectins influence many steps of cancer development by inducing the recruitment of immune cells to the inflammatory sites and modulating the effector function of neutrophils, monocytes, and lymphocytes. Recent studies described that different isoforms of galectins can induce platelet adhesion, aggregation, and granule release through the interaction with platelet-specific glycoproteins and integrins. Patients with cancer and/or deep-venous thrombosis have increased levels of galectins in the vasculature, suggesting that these proteins could be important contributors to cancer-associated inflammation and thrombosis. In this review, we summarize the pathological role of galectins in inflammatory and thrombotic events, influencing tumor progression and metastasis. We also discuss the potential of anti-cancer therapies targeting galectins in the pathological context of cancer-associated inflammation and thrombosis.